Improved Smart Pseudoscopic-to-Orthoscopic Conversion Algorithm for Integral Imaging With Pixel Information Averaging - Mao, Yan; Wang, Weifeng; Jiang, Xiaoyu; Yan, Zhan; Wang, Chenqing; Yan, Xingpeng (Frontiers in Physics, 2021)
The smart pseudoscopic-to-orthoscopic conversion (SPOC) algorithm can synthesize a new elemental image array (EIA) using the already captured EIA, but the algorithm only relies on one simulated ray to establish the mapping relationship between the display pixels and the synthetic pixels. This paper improves the SPOC algorithm and proposes the average SPOC algorithm, which fully considers the converging effect of the synthetic lens on the ray. In the average SPOC algorithm, the simulated rays start from the synthetic pixel, pass through the upper and lower edge of the corresponding synthetic lens, and intersect the display lenses respectively. Then, the value of the synthetic pixel is equivalent to the average value of display pixels which correspond to the display lenses covered by the rays. Theoretical analysis points out that the average SPOC algorithm can effectively alleviate the matching error between the display pixels and the synthetic pixels, thereby improving the accuracy of the synthetic elemental image array (SEIA) and the reconstruction effect . According to the experimental results we get, the superiority of the average SPOC algorithm is verified.